Improvement of the pitch bearing load distribution by shape-optimized stiffening plates. Issue 5 (September 2020) - Loriemi, A; Jacobs, G; Bosse, D; Zweiffel, M
Abstract: Due to a small cross-sectional dimension compared to their diameter, pitch bearings have a comparably low stiffness. Therefore, surrounding structures strongly influence the internal load distribution of the bearing. By the use of stiffening plates, the load situation of pitch bearings can be positively affected. With a gradient-based optimization procedure regarding contact force and contact angle distribution, an optimized plate shape is determined. This optimized shape provides at the same time a more equalized load distribution, while minimizing the effect of contact ellipse truncation.